2022
DOI: 10.1158/1078-0432.ccr-22-0339
|View full text |Cite
|
Sign up to set email alerts
|

Phase IB Study of GITR Agonist Antibody TRX518 Singly and in Combination with Gemcitabine, Pembrolizumab, or Nivolumab in Patients with Advanced Solid Tumors

Abstract: Purpose: TRX518 is a monoclonal antibody engaging the glucocorticoid-induced tumor necrosis factor receptor-related protein (GITR). This open-label, phase I study (TRX518-003) evaluated the safety and efficacy of repeated dose TRX518 monotherapy and combination with gemcitabine, pembrolizumab or nivolumab in advanced solid tumors. Experimental Design: TRX518 monotherapy was dose-escalated (Part A) and expanded (Part B) up to 4 mg/kg load, 1 mg/kg Q3W. Parts C-E included dose-escalation (2mg/kg and 4 mg/kg load… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 62 publications
(94 reference statements)
0
13
0
Order By: Relevance
“…The data demonstrated that T cell reinvigoration with PD-1 blockade can overcome resistance of advanced tumours to anti-GITR monotherapy [ 528 ]. Another phase Ib study using the GITR agonist (TRX518) alone and in combination with gemcitabine, pembrolizumab or nivolumab showed that TRX518 monotherapy + anti-PD1 combination was associated with intratumoral T regs reductions and CD8 + increases and activation in patients with advanced solid tumours [ 529 ]. The safety, tolerability and potential clinical activity of a GITR agonist (BMS-986156) alone or in combination with nivolumab in patients with advanced solid tumours was also a focus of a phase I/IIa dose-escalation and cohort-extension clinical trial (NCT02598960).…”
Section: Resultsmentioning
confidence: 99%
“…The data demonstrated that T cell reinvigoration with PD-1 blockade can overcome resistance of advanced tumours to anti-GITR monotherapy [ 528 ]. Another phase Ib study using the GITR agonist (TRX518) alone and in combination with gemcitabine, pembrolizumab or nivolumab showed that TRX518 monotherapy + anti-PD1 combination was associated with intratumoral T regs reductions and CD8 + increases and activation in patients with advanced solid tumours [ 529 ]. The safety, tolerability and potential clinical activity of a GITR agonist (BMS-986156) alone or in combination with nivolumab in patients with advanced solid tumours was also a focus of a phase I/IIa dose-escalation and cohort-extension clinical trial (NCT02598960).…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, GITR represents an ideal targetable immunomodulatory receptor that could provide a powerful tool to diminish the suppressive potential of intratumoral Treg and enhance anti-tumor immunity. Of note, different clinical trials are testing GITR agonist antibodies in combination with immune checkpoint inhibitors in advanced tumors (92)(93)(94)(95). On this basis, considering the increased frequencies of NK and T cells expressing GITR, the use of agonistic GITR combined with blocking PD-1 and/or TIGIT antibodies could be beneficial in patients with HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…TRX‐518 (also known as Tab6C8 in the manuscript), its murine surrogate mAb was shown effective in the B16 melanoma model with monotherapy (6C8, Leap Therapeutics, Cambridge, MA, USA; US20170137527 A1). TRX518 monotherapy and in combination showed limited clinical responses associated with immune activation in clinical studies [ 39 ]. Mouse GITR has been shown to signal effectively as a dimer while, in contrast, human GITR requires trimerization [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%